Profil Keterampilan Berpikir Kritis Siswa Salah Satu SMA Swasta di Sragen pada Materi Sistem Reproduksi - Eka Supriyati; Oktaviana Eka Setyawati; Dwi Yuli Purwati; Lintang Sirfa Salsabila; Baskoro Adi Prayitno (Bioedukasi: Jurnal Pendidikan Biologi, 2018)
This study aims to find out the profile of critical thinking skills of a private high school students in Sragen on reproduction system material. This study used survey method. The population in this study is all students of XI MIPA class. The sampling used purposive random sampling with the total sample of 24 students. The instrument used in form of a written tests refers to the indicators of critical thinking which developed by Ennis. The indicators of critical thinking skills measured are : (1) Elementary clarification; (2) Basic support; (3) Inference; (4) Advanced clarification; and 5) Strategies and tactics. Data analysis techniques use descriptive statistics. The results showed that in general, the average critical thinking skills of one of the private high school students in Sragen is in the high category.